Integrating Multicultural Education and Islam Wasathiyah: Strategies for Fostering Inclusive Children's Educational Environments - Anik Faridah; Hasan Ruzakki; Umi Rosyidah; Mudrik Al Farizi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Globalization has intensified the complexity of fostering inclusive education, particularly in culturally diverse societies. Multicultural education promotes respect and appreciation for diversity, while Islam Wasathiyah—a principle rooted in Islamic teachings—emphasizes moderation, balance, and universal values. This study explores the integration of these two frameworks to develop a culturally grounded model for inclusive education. A systematic literature review was conducted to examine scholarly works on multicultural education and Islam Wasathiyah. Sources were selected based on relevance, credibility, and their contribution to inclusive educational practices. Findings suggest that combining multicultural education with Islam Wasathiyah provides a cohesive framework to support inclusivity in schools. This integration enhances social harmony, promotes tolerance, and fosters inclusive, child-friendly learning environments. Key strategies identified include diversity-sensitive teacher training, curriculum development based on shared human values, and active community participation in educational initiatives. By bridging cultural and religious educational paradigms, this model offers a universally adaptable approach to inclusivity. It contributes to broader educational reforms aimed at nurturing empathy and coexistence in pluralistic societies. The strategic fusion of these principles addresses gaps in current inclusive education practices and offers practical implementation pathways. Integrating Islam Wasathiyah with multicultural education creates a holistic model for inclusive education that is both culturally sensitive and universally applicable. This approach supports the development of equitable education systems responsive to cultural and religious diversity in today’s global context.